2015
DOI: 10.1021/acsami.5b08004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Screen of Metal Oxide Nanoparticles for DNA Adsorption, Fluorescence Quenching, and Anion Discrimination

Abstract: While DNA has been quite successful in metal cation detection, anion detectioin remains challenging due to the charge repulsion. Metal oxides represent a very important class of materials, and different oxides might interact with anions differently. In this work, a comprehensive screen of common metal oxide nanoparticles (MONPs) was carried out for their ability to adsorb DNA, quench fluorescence, and release adsorbed DNA in the presence of target anions. A total of 19 MONPs were studied, including Al2O3, CeO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 44 publications
4
127
0
Order By: Relevance
“…DNA is a polyanion with a phosphate backbone, and previous studies suggested that DNA adsorption by a few oxides (e.g. CeO 2 , Fe 3 O 4 , and TiO 2 ) occurred mainly via its phosphate backbone [24,25,29,30]. Figure 1b depicts such an interaction.…”
Section: Selenite Is Adsorbed More Strongly By Different Metal Oxidesmentioning
confidence: 87%
See 1 more Smart Citation
“…DNA is a polyanion with a phosphate backbone, and previous studies suggested that DNA adsorption by a few oxides (e.g. CeO 2 , Fe 3 O 4 , and TiO 2 ) occurred mainly via its phosphate backbone [24,25,29,30]. Figure 1b depicts such an interaction.…”
Section: Selenite Is Adsorbed More Strongly By Different Metal Oxidesmentioning
confidence: 87%
“…For example, it is well known that arsenate has a strong affinity with iron oxide and this has been used for remediation of arsenic species from the environment [23]. We took advantage of the competitive adsorption of DNA and arsenate for its detection [24][25][26]. Similarly, hydrogen peroxide can displace DNA from cerium oxide [27], while fluoride can enhance its catalytic activity [28].…”
Section: Introductionmentioning
confidence: 99%
“…The covalent binding involves a cross-linking agent between ZnO surface and molecules of the bioselective layer, which provides a significant structure of the bioselective layer and improves the biorecognition [89,47,78,81,87,88].…”
Section: Covalent Binding Between Zno Surface and Biomoleculesmentioning
confidence: 99%
“…Amine (-NH2) and thiol (-SH2) groups are formed after treatment with aminosilanes and mercaptosilanes, respectively [47,89]. The direct immobilization of protein through the interaction between amine and carboxyl groups after APTES silanization of ZnO surface has been investigated as well [78,81]. In the case of thiol-based silanizated ZnO surface, one more step needed for a protein immobilization [47,89].…”
Section: Silanizationmentioning
confidence: 99%
“…For example, DNA uses its phosphate to adsorb onto many metal oxides, 45 while uses its base coordination to bind to gold nanoparticles. 46 To probe possible chemical interactions, we next challenged the samples with 10 mM free inorganic phosphate or 1 mM adenosine.…”
Section: Dna Desorptionmentioning
confidence: 99%